2004
DOI: 10.1042/bj20040231
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a stretch of six divergent amino acids on the alpha5 helix of Galpha16 as a major determinant of the promiscuity and efficiency of receptor coupling

Abstract: A broad repertory of G-protein-coupled receptors shows effective coupling with the haematopoietic G16 protein. In the present study, individual residues along the C-terminal alpha5 helix of Galpha16 were examined for their contributions in defining receptor-coupling specificity. Residues that are relatively conserved within, but diverse between, the subfamilies of cloned Galpha subunits were mutated into the corresponding Galpha(z) residues. Six G(i)-linked receptors with different coupling efficiencies to Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Biochemical, kinetic, and structural characterizations have identified binding sites for GPCR on the G␣ subunit (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). This contiguous surface includes the N terminus (2-7), the ␣4-␤6 loop (8 -13), the ␣3-␤5 loop (14), and the C terminus of G␣ (3) and is located Ͼ30 Å away from the guanine nucleotide binding site (15)(16)(17) (Fig.…”
mentioning
confidence: 99%
“…Biochemical, kinetic, and structural characterizations have identified binding sites for GPCR on the G␣ subunit (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). This contiguous surface includes the N terminus (2-7), the ␣4-␤6 loop (8 -13), the ␣3-␤5 loop (14), and the C terminus of G␣ (3) and is located Ͼ30 Å away from the guanine nucleotide binding site (15)(16)(17) (Fig.…”
mentioning
confidence: 99%
“…(v) The serotonin 5-HT1B receptor couples to G protein heterotrimers containing either Gαi1, Gαi2, Gαi3, or Gαo but not Gαt although their Ctermini are highly homologous [71]. To date, at least 4 other regions within Gα have been shown to be involved in receptor interaction: The amino-terminal domain [21,[72][73][74], the α2 helix and α2-β4 loop regions [26,27], the α4 helix and α4-β6 loop domain [26,28,61,75,76], the α5 helix [77,78], the α3-β5 region [79], and a small segment within the loop linking the N-terminal α helix to the β1 strand of the ras-like domain [32]. Of those, the extreme N-and Ctermini, the αN-β1 loop, the α4-β6 region, and the α5 helix contribute to the specificity of Gα-receptor interaction ( Fig.…”
Section: Analyzing Receptor-g Protein Specifi-city With Gα Chimeras: mentioning
confidence: 99%
“…Interestingly, most of the GPCRs that fail to interact with Gα16 are Gi-selective [for a comprehensive list see refs in 76,98,99]. Therefore attempts have been made to increase the promiscuity of Gα16 towards the Gi family of receptors [76,78,99]. Mody et al [76] created a series of chimeras between Gα16 and Gαz and identified two chimeric Gα proteins to be particularly useful: Gα16z25 and Gα16z44 in which the sequence of the α4-β6 and α5 regions were derived from Gαz.…”
Section: Naturally Promiscuous Gα14 Gα15 and Gα16 Proteinsmentioning
confidence: 99%
“…Further efforts have been made to decipher the minimal requirements for switching the receptor-coupling specificity. Individual residue lying on the exposed surface of the ␣ 5 helix of G ␣ 16 , as well as a stretch of six amino acids between the ␣ 5 helix and the extreme C-terminal tail, plays an important role in determining the receptor-coupling specificity [30] . Other potential receptor-interacting regions on G ␣ 16 have also been explored, such as the ␤ 2/ ␤ 3 loop [30] , ␣ N/ ␤ 1 loop [31] , as well as the uniquely long ␣ 4/ ␤ 6 loop ( fig.…”
Section: Promiscuous Receptor Coupling Of G 16mentioning
confidence: 99%
“…The same strategy worked equally well for G s -coupled receptors [27] . Chimeric G ␣ 16 subunits with broadened receptor-coupling capability have been successfully employed in high throughput screening platforms [23,[28][29][30] . Further efforts have been made to decipher the minimal requirements for switching the receptor-coupling specificity.…”
Section: Promiscuous Receptor Coupling Of G 16mentioning
confidence: 99%